Pengaruh Pemberian Mol Sabut Kelapa Terhadap Pertumbuhan Tanaman Sawi Pakcoy (Brassica rapa L.) - Afif Ramadhana Danie; Diane D. Pioh; Rafli Kawulusan; Adeleyda M. W. Lumingkewas (COCOS, 2019)
ABSTRACTSoil fertility is very necessary in the process of plant growth. This study aims to find theeffect of giving coconut fiber MOL to the growth of pakcoy mustard plants(Brassica Rapa L.). Thisresearch was conducted from December 2019 to February 2020 at the Greenhouse of the Faculty ofAgriculture, Sam Ratulangi University, Manado. The method used in this research is a CompletelyRandomized Design (CRD) method with 6 treatments that were repeated 3 times. The treatmentused consist of K: Control, P: Phonska 250 kg/ha, M25: Coconut fiber MOL solution 25% +phonska 250 kg/ha, M50: Coconut fiber MOL solution 50% + phonska 250 kg/ha, M75: Coconutfiber MOL solution 75% + phonska 250 kg/ha, dan M100: Coconut fiber MOL solution 100% +phonska 250 kg/ha. The results showed that the administration of coconut fiber MOL on thegrowth of mustard pakcoy plants in the concentration of coconut fiber MOL 75% + phonska 250kg / ha had an influence on plant height and for the concentration of coconut coir MOL 25% +phonska 250kg / ha had an influence on the number of leaves and weight wet even though thestatistical results show no significant difference.Keywords: Brassica rapa L., Solution, Coconut fiber MOL.